2001
DOI: 10.1103/physrevlett.86.5062
|View full text |Cite
|
Sign up to set email alerts
|

Dilation-Induced Phases of Gases Absorbed within a Bundle of Carbon Nanotubes

Abstract: A study is presented of the effects of gas (especially H2) absorption within the interstitial channels of a bundle of carbon nanotubes. The ground state of the system is determined by minimizing the total energy, which includes the molecules' interaction with the tubes, the intertube interaction, and the molecules' mutual interaction (which is screened by the tubes). The consequences of swelling include a reduced threshold pressure for gas uptake and a 2.7% increase in the tubes' breathing mode frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 21 publications
(33 reference statements)
3
56
2
Order By: Relevance
“…In our simulations, no phase transition occurred, which is different from the case mentioned by Cole and co-workers. 33,34 They believed that the geometry variation of adsorbents should be taken into account, if the simulation was implemented at lower temperatures than the critical point.…”
Section: Fitting Of the Force Fieldmentioning
confidence: 99%
“…In our simulations, no phase transition occurred, which is different from the case mentioned by Cole and co-workers. 33,34 They believed that the geometry variation of adsorbents should be taken into account, if the simulation was implemented at lower temperatures than the critical point.…”
Section: Fitting Of the Force Fieldmentioning
confidence: 99%
“…A A systematic up-shift of the RB modes of single walled CNT's has been associated to intertubular interaction and distortion in bundles [23] and theoretical calculations indicate a up-shift of upto 10% for tubes in bundles [24]. Furthermore a theoretical study has recently shown that gas absorption within the interstitial channels of a bundele of CNTs can increase the RB mode energy [25,26] by 2.7%. This can certainly influence the position of the RB modes of the external tunbes but less likely the RB modes of the internal tubes.…”
mentioning
confidence: 99%
“…This is also the case for almost all simulations of adsorption on SWNTs. 156,160,[162][163][164]192,[200][201][202] Interpretation of the experimental data in terms of this idealized model of SWNT bundles has lead to the conclusion that gases do not adsorb in the interstitial channels (ICs) of bundles. 35 Theory, based on homogeneous bundles, predicts that small molecules such as H 2 , He, and Ne will adsorb in the ICs, but that larger molecules, such as CH 4 , Ar, and Xe, are too large to enter the ICs.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the theoretical calculations to date have assumed that nanotubes in the bundles have identical diameters (homogeneous) and are packed in perfect 2-d hexagonal arrays. 156,160,[162][163][164]192,[200][201][202] This simple model is also invoked by many experimentalists to interpret experimental data. 36,38,40,42 We have shown in our previous paper 47 that SWNT bundles composed of heterogeneous nanotubes with diameter distributions similar to those observed in experiments always exhibit packing defects.…”
mentioning
confidence: 95%